Bifunctional covalent bromine: an advanced redox mediator for rechargeable lithium–oxygen batteries. Issue 98 (21st November 2022) - Li, Chu-Yue; Wu, Min-Sheng; Chen, Wei-Rong; Rong, Yuan-Jia; Wang, Qian-Yan; Zhang, Xiao-Ping
Abstract : In this work, we introduce trimethylbromosilane (C3 H9 SiBr), which can protect lithium metal anodes via an in situ formed SEI layer while catalyzing the decomposition of Li2 O2 . Abstract : In this work, we introduce trimethylbromosilane (C3 H9 SiBr), which can protect lithium metal anodes via an in situ formed SEI layer while catalyzing the decomposition of Li2 O2 . As a result, lithium–oxygen batteries with C3 H9 SiBr offer a long cycle life of 110 cycles with a significantly reduced charging/discharging overpotential.